2009
DOI: 10.1161/circulationaha.108.768986
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence

Abstract: Abstract-Medication adherence usually refers to whether patients take their medications as prescribed (eg, twice daily), as well as whether they continue to take a prescribed medication. Medication nonadherence is a growing concern to clinicians, healthcare systems, and other stakeholders (eg, payers) because of mounting evidence that it is prevalent and associated with adverse outcomes and higher costs of care. To date, measurement of patient medication adherence and use of interventions to improve adherence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

25
616
2
23

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,251 publications
(702 citation statements)
references
References 72 publications
(69 reference statements)
25
616
2
23
Order By: Relevance
“…Many randomized, control trials demonstrated the benefit of antihypertensive medications (antihypertensives) on reduction of risk for CVD morbidity and mortality 2, 3. Despite the benefit of antihypertensive therapies, many studies suggested suboptimal adherence to these medications, particularly among older adults with multiple chronic conditions 4, 5, 6, 7, 8, 9, 10, 11. Nonadherence to antihypertensives is associated with increased risk for CVD, hospitalization, and healthcare costs 5, 12, 13, 14, 15, 16, 17.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many randomized, control trials demonstrated the benefit of antihypertensive medications (antihypertensives) on reduction of risk for CVD morbidity and mortality 2, 3. Despite the benefit of antihypertensive therapies, many studies suggested suboptimal adherence to these medications, particularly among older adults with multiple chronic conditions 4, 5, 6, 7, 8, 9, 10, 11. Nonadherence to antihypertensives is associated with increased risk for CVD, hospitalization, and healthcare costs 5, 12, 13, 14, 15, 16, 17.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the benefit of antihypertensive therapies, many studies suggested suboptimal adherence to these medications, particularly among older adults with multiple chronic conditions 4, 5, 6, 7, 8, 9, 10, 11. Nonadherence to antihypertensives is associated with increased risk for CVD, hospitalization, and healthcare costs 5, 12, 13, 14, 15, 16, 17. Many observational studies examined the relationship between antihypertensive adherence and CVD outcomes in the general hypertension population 5, 13, 17.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2000 years since, it remains unclear how much progress has been made. Research shows that medication nonadherence remains highly prevalent and is associated with adverse outcomes and higher costs of care 2, 3. For example, a year after sustaining an acute myocardial infarction, less than 50% of patients are filling prescriptions for statin, beta‐blocker, and angiotensin‐converting‐enzyme inhibitor medications, even when these medications are offered with no copay 4.…”
mentioning
confidence: 99%
“…One of the common features of successful interventions has been regular follow‐up with healthcare providers, often through focused heart failure disease management clinics 3. Given the burden of medication initiation with new and worsening heart failure and issues with polypharmacy, transitions from hospital‐to‐home after a hospital admission for heart failure decompensation are particularly vulnerable periods for patients.…”
mentioning
confidence: 99%